Condition Of Transportation At Large Intersections - Sherko'zieva G.F; Bakhriddinova M.N; Egamberdieva Z.Z; Toshpulatov B.M; Abdurashidova D; Boysariyeva M.R; Rasulov R.S (Academia One, 2025)
This article provides information about vehicles, one of the main pollutants of atmospheric air, which is one of the environmental factors on major urban highways, and their specific aspects. At the same time, the level of pollution of the air basin with vehicle exhaust gases at major urban intersections was studied using a calculation method
Keywords: motor vehicle; hygienic standard; highway